Jatkuva integraatio ja testaaminen ohjelmistokehityksessä : systemaattinen kirjallisuuskartoitus - Hepola, Mikko (2023)
Continuous integration is a widely employed practice aimed at achieving rapid and high-quality software development. The core principle of continuous integration is to ensure the compatibility of software changes with the existing implementation, thereby confirming the functionality of the application even after modifications. This study investigated the research conducted on testing related to continuous integration. Through a systematic mapping study, 52 articles were selected to address the research question: What is the current state of research on testing related to continuous integration? Two main categories were identified from the data, with one emphasizing continuous integration and the other focusing on testing. Based on the articles included in the study, research on testing related to continuous integration appears diverse, and there seems to be consensus on the practical principles of continuous integration. In general, continuous integration was perceived as beneficial because it saves time and improves error detection. Some studies aimed to find alternatives for running tests in continuous integration, as the challenge was seen in the duration and costs of running tests, especially in larger projects.